Pengembangan Kurikulum Berbasis Literasi Digital Untuk Meningkatkan Keterampilan Abad Ke 21 Pada Peserta Didik Sekolah Menengah Atas - Marjanah Marjanah; Saldin Saldin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The digital era demands educational transfossrmation to facilitate students in developing 21st-century skills. This research aims to formulate a digital literacy-based curriculum development model at the high school level to enhance critical thinking, creativity, communication, and collaboration skills. This study uses a qualitative approach with a literature review method. Data were obtained through a critical analysis of various relevant scientific literature sources such as journals, books, and educational policy documents. The study results indicate that a curriculum that systematically integrates digital literacy can improve students' 21st-century skills. This study provides a recommendation for high school curricula to adopt a digital and contextual-based learning approach.